Death of an Icon: Deconstructing the Irish Harp Emblem in the Celtic Tiger Years - O’Donnell, Mary Louise (Journal of the Society for Musicology in Ireland, 2013)
The Irish harp emblem, adopted as the official emblem of Ireland following the foundation of the Irish Free State in 1922, has remained an image of continuity and stability in Irish politics and society for almost a century. Since the mid-1990s there have been considerable shifts in the representation of the Irish harp emblem, particularly in various government departments and quangos: e.g. the Department of Agriculture, Food and the Marine, the Department of Defence, the National Asset Management Agency (NAMA) and the National Treasury Management Agency. This article explores the shifting interpretations of the iconography of the emblem in the ‘Celtic Tiger’ years - and, more recently, in the economic downturn - and attempts to analyse critically these images as postmodern visual representations of changing political, social and cultural values over the last two decades. By drawing on the studies of Fredric Jameson, Jean Baudrillard and Charles Sanders Peirce, it argues that the deconstruction of the Irish harp emblem is indicative of a wider attempt to construct a new postmodern Irish identity.